LEGAL REVIEW ON THE POSITION AND FUNCTIONS OF REGIONAL SECRETARY IN REGIONAL GOVERNMENT IMPLEMENTATION (STUDY AT PUNCAK DISTRICT) - Arman Koedoeboen; Izac Zet Matulessy (Journal of International Islamic Law, Human Right and Public Policy, 2026)
This research analyzes the position and functions of the Regional Secretary (Sekda) in the regional government administration system based on statutory provisions and examines its implementation in Puncak District. Using normative legal research methods with statutory and conceptual approaches, this study analyzes Law No. 23 of 2014 on Regional Government, Government Regulation no. 18 of 2016 on Regional Apparatus, and current state administrative law literature. The findings show that the Regional Secretary has a strategic legal position as a staff element of regional government responsible for assisting the Regional Head in policy formulation and coordinating government implementation. Functionally, the Regional Secretary acts as an administrative law bridge between political policy and regional bureaucratic implementation. In practice in Puncak District, the Regional Secretary's function faces challenges including limited human resources, difficult geographic conditions, and local political dynamics. Nevertheless, the Regional Secretary has made optimization efforts through strengthening administrative systems, civil servant development, and implementing good governance principles. In conclusion, the Regional Secretary's function reflects the application of rule of law principles and serves as an important instrument in realizing effective, transparent, and accountable regional government governance. This study recommends strengthening administrative law capacity for regional officials and improving ASN professionalism to optimize Sekda's functions